Membaca Ulang Pendidikan Humanis (Literacy Pendidikan Humanis) (Forum Ilmu Sosial, 2016)
Humanist education according to several genre and some experts, the author does not deliver the best one genre but offer several options of humanist education. The Renaisance was born around 15-16 century, when the intellectual, political, and artists in Europe simultaneously conduct a reform movement who want the freedom of thought to change the religious doctrines which so restrictive inner freedom. The contradict humand mind dogma has tried and is strongly opposed by the thinkers' leaders of  that era, during the Renaisance human found 2 things : the world and himself, self- introduction means that aware of the self values and individual strenth, the heir of the Renaisance movemnet is Humanisme, the term of Humanisme derives from word “Human” which means man. The genre of the Humanist education is devided to the several namely: religious Humanist education, secular Humanist education era and the Humanist genre which was delivered by the figures of national education. The Humanis secular genre  is an educational genre which emphasizes the freedom of creation and expression which is sparated from dogma, the core of this educational genre that distinguishes and separates between education and religion, the resources referenced are the rights and freedom of human expression based on the idea. While the religion Humanist education which emphasized to the Human educational attainment without leaving the faith. The Humanist education in Javaness Philosphy is how the humans maintain harmony and balance in the world, also the balance and the worlds' harmony.